If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 17t + -1 = 6t + 34 + -2t Reorder the terms: 9 + -1 + 17t = 6t + 34 + -2t Combine like terms: 9 + -1 = 8 8 + 17t = 6t + 34 + -2t Reorder the terms: 8 + 17t = 34 + 6t + -2t Combine like terms: 6t + -2t = 4t 8 + 17t = 34 + 4t Solving 8 + 17t = 34 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 8 + 17t + -4t = 34 + 4t + -4t Combine like terms: 17t + -4t = 13t 8 + 13t = 34 + 4t + -4t Combine like terms: 4t + -4t = 0 8 + 13t = 34 + 0 8 + 13t = 34 Add '-8' to each side of the equation. 8 + -8 + 13t = 34 + -8 Combine like terms: 8 + -8 = 0 0 + 13t = 34 + -8 13t = 34 + -8 Combine like terms: 34 + -8 = 26 13t = 26 Divide each side by '13'. t = 2 Simplifying t = 2
| 2x+33=75-5x | | 7x+5(x+9)= | | 18x^2y^3+24xy^5= | | 11(t-3)+7t=6(3t+3)-9 | | -4a(3a-5a)=0 | | -3(v-3)=5v+17 | | 5+18a=77 | | 16-4ln(3x)=20 | | 7(x+9)+5x= | | 3y=8x+1 | | 36+6n=-6(1-8n) | | x^2+12=24+x | | x-8.8=6.1 | | 2x+6(-2x-4)=-29-5x | | log[4](-4x)=1 | | 11e-12+9e-16=13e+42 | | 7x+5(x-9)= | | -5x+165=-3x+153 | | -6(-6+4x)=3x-18 | | 44428=974x+17156 | | 97=-7(x-7)-5x | | 2x^2-12x-34=0 | | 15x=9x+24 | | -6(4+6x)=-4x-24 | | 24x^2-40x-56=0 | | 52/7-5/14 | | 18-5x-2=-4 | | 7-(m-2)=12 | | 20Q+800=100+Q | | (2x-5)(3x^2-4x+1)=0 | | z^2+10z+11=0 | | 5(x+6)+1=3-2x |